Comparison of mid-age-onset and late-onset Huntington's disease in Finnish patients - Jussi O. T. Sipilä; Tommi Kauko; Markku Päivärinta; Kari Majamaa (SPRINGER HEIDELBERG, 2022)
The phenotype of juvenile Huntington's disease (HD) differs clearly from that of adult-onset HD, but information about differences between mid-age-onset HD and late-onset HD (LOHD) is scarce. A national cohort of 206 patients with adult-onset HD was identified using national registries and patient records. LOHD was defined as age >= 60 years at HD diagnosis. Genetic disease burden was assessed using CAG age product (CAP) score. LOHD comprised 25% of the adult-onset HD cohort giving a point prevalence of 2.38/100,000 in the Finnish population at least 60 years of age. The proportion of LOHD out of new HD diagnoses increased from 21% in 1991-2000 to 33% in 2001-2010. At the time of diagnosis, patients with LOHD had 10.4 units (95% CI 4.8-15.9; p = 0.0003) higher CAP scores, more severe motor impairment and slightly more severe functional impairment than that in patients with mid-age-onset HD. There was no difference in the rate of disease progression or survival between LOHD and mid-age-onset patients. The lifespans of deceased patients were shorter in mid-age-onset HD (p < 0.001) and LOHD (p = 0.002) than their life expectancies. Causes of death differed between the two patient groups (p = 0.025). LOHD comprises a quarter of Finnish HD patients and the proportion appears to be increasing. Our results did not reveal differences in the phenotype between mid-age-onset HD and LOHD, but prospective studies are needed.